Predicting Parent Trust Based on Professionals' Communication Skills - James Edward Hamm; Angela DeSilva Mousseau (MDPI AG, 2023)
Trust is critical to the establishment and maintenance of working relationships between the parents of children with disabilities and their child's professional. Knowledge of the specific communication skills needed to secure trust is unclear. The current study investigated the relationship between parent evaluation of professionals' communication skills and parent trust of professionals. A total of 165 parents responded to an online survey during the COVID-19 pandemic. The results indicated that professionals' communication skills had a significant and moderately positive relationship with the parent trust of professionals. Hierarchical multiple regression analyses indicated that parents' ratings of professionals' communication competence, and professionals' use of in-person communication were the only predictors of parent trust of special education professionals, even when other factors were considered. This study's findings draw attention to the importance communication skills may have in establishing and maintaining trusting relationships with parents.